Msme Development Through Social Media - Raihan, Muhamad; Nasution , Muhammad Irwan Fadli; Sundari, Sri Suci Ayu (LPPM Universitas Bina Bangsa, 2024)
The majority of Indonesian people now get news and information from social media sites. The use of social media as a promotional tool has been documented in numerous examples. However, successfully using social media for promotional purposes is not just a snap of the palm. Many people quickly give up after trying social media marketing. To help small businesses reach a wider audience, this article will provide a social media approach. Lardi's Social Media Strategy Framework was used at every stage of the research process, which included interviews, observation, and reading of relevant literature. As a result of this research, small businesses will have access to social media expansion techniques. It is hoped that small business actors will get some insights about how and for what to use social media from the social media plans that have been developed.